Gene expression changes in aging retinal microglia: relationship to microglial support functions and regulation of activation - Ma, Wenxin (2013)
Microglia, the resident immune cell of the central nervous system (CNS), are thought to contribute to the pathogenesis of age-related neurodegenerative disorders. It has been hypothesized that microglia undergo age-related changes in gene expression patterns that give rise to pathogenic phenotypes. We compared the gene expression profiles in microglia isolated ex vivo from the mouse retinas of ages ranging from early adulthood to late senescence. We discovered that microglial gene expression demonstrated progressive change with increasing age and involved genes that regulate microglial supportive functions and immune activation. Molecular pathways involving immune function and regulation, angiogenesis, and neurotrophin signaling demonstrated age-related change. In particular, expression levels of complement genes, C3 and CFB, previously associated with age-related macular degeneration (AMD), increased with aging, suggesting that senescent microglia may contribute to complement dysregulation during disease pathogenesis. Taken together, senescent microglia demonstrate age-related gene expression changes capable of altering their constitutive support functions and regulation of their activation status in ways relating to neuroinflammation and neurodegeneration in the CNS.